Reviewing the mechanism of action and results of clinical studies on the antifungal drug ibrexafungerp - L. I. Tagirova; K. R. Farvazova; D. R. Valeeva; M. D. Orlova; I. A. Gubaidullin; A. M. Tulyabaeva; A. R. Abdulmanova; R. V. Tryapko; D. A. Shelyginsky; A. R. Khanafieva; N. G. Semenova; E. M. Takiullin (IRBIS LLC, 2024)
Introduction. Vulvovaginal candidiasis is an extremely common pathology of the female genital organs, leading to a long-term recurrent course and multiple complications. Although currently it is widely known about developing antibiotic resistance of bacterial pathogens, it is necessary to remember about similar phenomenon observed in other groups of infectious agents. In this regard, fungal infection also requires development of new therapeutic techniques and medicinal antifungal drugs, such as ibrexafungerp.   Aim: to analyze available publications revealing the mechanism of action, efficacy, antifungal spectrum and results of clinical trials for a new oral antifungal drug ibrexafungerp.   Materials and Methods. A search for publications in the electronic databases PubMed, eLibrary and ClinicalTrials.gov, published over the last 25 years was conducted using the following keywords in Russian and English: "candidiasis", "vulvovaginal candidiasis", "antifungal drugs", "ibrexafungerp", "clinical trials", "mechanism of action". Articles were assessed according to PRISMA guidelines. The titles and abstracts of identified publications were independently reviewed to retrieve relevant full text studies. After the selection procedure, 46 articles were included in the review.   Results. This review provides information on the creation of the drug ibrexafungerp, its mechanism of action, the activity against a relatively wide range of pathogens, as well as the results from 13 ongoing and completed clinical trials in patients with fungal infection.   Conclusion. The analysis of ibrexafungerp-related clinical studies showed its good oral bioavailability, high antifungal efficacy, so that its one-day dosage may further eliminate a need for unnecessarily long hospitalization and complex dosing schedules, thereby increasing adherence to therapy and odds for treatment success.